Assessment of the genetic diversity of Xylella fastidiosa in imported ornamental Coffea arabica plants. (21st March 2017) - Bergsma‐Vlami, M.; van de Bilt, J. L. J.; Tjou‐Tam‐Sin, N. N. A.; Helderman, C. M.; Gorkink‐Smits, P. P. M. A.; Landman, N. M.; van Nieuwburg, J. G. W.; van Veen, E. J.; Westenberg, M.
Abstract : A study was performed in order to assess the presence of Xylella fastidiosa in imported ornamental plants, among them Olea europaea, Coffea arabica and Nerium oleander . Positive results were only obtained from C. arabica, where 15 plant samples tested positive for X. fastidiosa by PCR, nine from Costa Rica and six from Honduras. Transmission electron microscopy observations indicated that rod‐shaped bacterial cells exhibiting the characteristics of X. fastidiosa cells were present in the xylem vessels of leaf petioles obtained from the infected C. arabica plants. Diversity of X. fastidiosa in C. arabica plants was assessed through a multilocus sequence typing (MLST) analysis of seven housekeeping genes ( leuA, petC, lacF, cysG, holC, nuoL and gltT ) and compared with X. fastidiosa infecting different host plants worldwide. Based on this MLST analysis, the prevalence of different sequence types (STs) of X. fastidiosa in the C. arabica ornamental plants was demonstrated and related to different X. fastidiosa subspecies, underlining the risk of introducing additional genetic diversity for X. fastidiosa to Europe. ST53, related to X. fastidiosa subsp . pauca, was frequently found in these C. arabica samples. A second ST related to X. fastidiosa subsp. pauca, ST73, has been assessed in coinfection with ST53 in one individual plant. Additionally, ST72 and ST76, related to X. fastidiosa subsp. fastidiosa, have been recorded. Next to these previously described STs, a novel ST, namely ST77 has been revealed, related to X. fastidiosa subsp. fastidiosa . Isolation of X. fastidiosa from leaf petioles and midribs of infected C. arabica plants was successfully performed only after the application of an additional ultrasonication step during the extraction procedure. Based on this approach, a number of X. fastidiosa isolates were obtained and further characterized.